Biocompatibility of primers and an adhesive used for implant-retained maxillofacial prostheses: An in vitro analysis - Bonatto, Liliane da Rocha [UNESP]; Goiato, Marcelo Coelho [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Haddad, Marcela Filié; Chaves-Neto, Antonio Hernandes [UNESP]; Brito, Victor Gustavo Balera [UNESP]; dos Santos, Daniela Micheline [UNESP] (Elsevier, 2017)
Statement of problem Implant-retained maxillofacial prostheses should be biocompatible, regardless of the primers and adhesives used to bond the acrylic resin and facial silicone. The authors are unaware of any study evaluating the influence of these primers and adhesives on the biocompatibility of maxillofacial prostheses. Purpose The purpose of this in vitro study was to evaluate the cytotoxic effect of primers and an adhesive used to bond acrylic resin and facial silicone during the fabrication of implant-retained maxillofacial prostheses. Material and methods Twenty-eight circular specimens made of resin and silicone were fabricated, either bonded or nonbonded with primer and adhesive. The specimens were divided into 7 groups: resin; silicone; resin+silastic medical adhesive type A+silicone; resin+DC 1205 primer silicone; resin+Sofreliner primer+silicone; resin+DC 1205 primer+silastic medical adhesive type A+silicone; and resin+Sofreliner primer+silastic medical adhesive type A+silicone. Eluates of the materials tested were prepared by setting 4 specimens of each experimental group in Falcon tubes with medium and incubating at 37°C for 24 hours. The eluate cytotoxicity was evaluated by an assay of survival/proliferation ((3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide [MTT] test) in cultures of human keratinocytes. The levels of IL1, IL6, TNFα, and the chemokine MIP-1α were evaluated by enzyme-linked immunosorbent assay. The mRNA expressions for MMP-9, TGF-β, and collagen type IV were analyzed by the real time polymerase chain reaction. Data were submitted to analysis of variance with Bonferroni post hoc tests (α=.05). Results An increased cell proliferation was observed for the RAS group, with statistically significant differences (P<.001) compared with the unstimulated group. The RDCpS group showed the highest IL6 concentration values (P<.001). No significant statistical difference was found in the relative quantification of mRNA for collagen type IV, MMP9, or TGFβ between the groups (P>.05). Conclusions The RAS group showed the highest cell proliferation percentage, while the RDCpS group exhibited the highest IL6 concentration values. No detectable levels of IL1β, TNF α, or CCL3/MIP1α were observed. The tested materials showed no toxic effects on the HaCaT cell line.